2015
DOI: 10.1097/igc.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Three Polymorphisms of Vascular Endothelial Growth Factor (+936C > T, −460C > T, and −2578C > A) and Their Susceptibility to Ovarian Cancer

Abstract: This meta-analysis provides supportive evidence that the VEGF +936 C/T polymorphism may influence the risk for the development of OC in a protective model among whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…While the present meta-analysis was being conducted, Zhang et al [ 33 ] published a meta-analysis of the relationship between ovarian cancer risk and the three polymorphisms +936C/T, −460C/T, and −2578C/A. Similar to their results, we found that the CT genotype at +936C/T may act as a protective factor in Caucasian populations.…”
Section: Discussionsupporting
confidence: 87%
“…While the present meta-analysis was being conducted, Zhang et al [ 33 ] published a meta-analysis of the relationship between ovarian cancer risk and the three polymorphisms +936C/T, −460C/T, and −2578C/A. Similar to their results, we found that the CT genotype at +936C/T may act as a protective factor in Caucasian populations.…”
Section: Discussionsupporting
confidence: 87%
“…While such analyses have limitations, they can provide direction for future research ( 25 ). In the results from a newly published meta-analysis ( 26 ) the interaction between three different VEGF polymorphism variants and decreased risk for ovarian cancer was explored. It was concluded that one of these (VEGF +936>T) may be a protective factor for epithelial ovarian cancer among the white ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…[91] As for ovarian, gastric, oral, and prostate cancers, there is no evidence of VEGF-460 being related to them. [86,89,90,92] A meta-analysis of VEGF-460 and overall cancer susceptibility was reported in 2009 by Xu et al [79] They concluded that this SNP could contribute to elevated cancer risk in Asian populations. Most of the above meta-analysis conclusions were consistent with ours, but only for single cancer and less included literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have conducted meta-analyses to evaluate this link comprehensively. [79][80][81][82][83][84][85][86][87][88][89][90][91][92] Their meta-analysis was almost only for single cancer with small sample sizes. As far as we know, only one meta-analysis of VEGF-460 polymorphisms and overall cancer risk has been published, [79] but it was published earlier and included less studies.…”
Section: Introductionmentioning
confidence: 99%